2011
DOI: 10.1039/c1cp20718k
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical reduction of O2 in 1-butyl-1-methylpyrrolidinium bis(trifluoromethanesulfonyl)imide ionic liquid containing Zn2+ cations: deposition of non-polar oriented ZnO nanocrystalline films

Abstract: The influence of the Zn(2+) concentration and temperature on the electrochemical reduction of O(2) in a solution of zinc bis(trifluoromethanesulfonyl)imide (Zn(TFSI)(2)) salt in 1-butyl-1-methylpyrrolidinium bis(trifluoromethanesulfonyl)imide (PYR(14)TFSI) ionic liquid is presented. ZnO nanocrystalline films were then electrodeposited, under enhanced O(2) reduction, at temperatures in the 75-150 °C range. Their morphology, chemical composition, structural and optical properties were analyzed. In contrast to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 47 publications
4
23
0
Order By: Relevance
“…[37] This peculiarity might be ar esult of the interactions between the discharge product and ions from the IL, which are very likely to influencet he nucleation and growth of the discharge product in asimilarway to that observed and reported in the case of ZnO [20,39] and NiO. [37] This peculiarity might be ar esult of the interactions between the discharge product and ions from the IL, which are very likely to influencet he nucleation and growth of the discharge product in asimilarway to that observed and reported in the case of ZnO [20,39] and NiO.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…[37] This peculiarity might be ar esult of the interactions between the discharge product and ions from the IL, which are very likely to influencet he nucleation and growth of the discharge product in asimilarway to that observed and reported in the case of ZnO [20,39] and NiO. [37] This peculiarity might be ar esult of the interactions between the discharge product and ions from the IL, which are very likely to influencet he nucleation and growth of the discharge product in asimilarway to that observed and reported in the case of ZnO [20,39] and NiO.…”
Section: Resultsmentioning
confidence: 71%
“…[11] Aside from classical electrolytes based on cyclic and acyclic carbonates, ionic liquids (ILs) such as hydrophobic and aprotic N-butyl-N-methylpyrrolidiniumb is(trifluoromethanesulfonyl)imide (PYR14TFSI) have also been considered because of their potentially attractive physicochemical properties, [12][13][14] which make them suitable candidates for technological development based on green, safe, and sustainable chemistry. There are af ew reports about using the electrochemical reduction of O 2 in ILs containing metal cations( i.e., Zn 2 + , [20,21] Ni 2 + , [22] Ce 4 + [23] )t od eposit metal oxide films [Eqs. Several groups [16][17][18][19] have investigated this aspect and concluded that in ILs free of metal cations the generationofs uperoxides firstly and peroxides subsequently occur accordingly to Equations (1) and (2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 shows the CV scans recorded in a solution containing 5 mM of ZnCl 2 , 0.1 M of KCl and a variable concentration of H 2 O 2 (2, 5, 7, 10 and 15 mM). During forward scan, from À 0.6 V a cathodic current observed relating to the formation of the hydroxides ions as following [24]:…”
Section: Cyclic Voltammetricstudymentioning
confidence: 98%
“…For the electrodeposition of ZnO, the majority of the published works used nitrate ions [17,20] or molecular oxygen as precursors in aqueous [21,22] and non-aqueous solvents [23,24]. However, few studies have been presented using hydrogen peroxide as a precursor [14,25,26].…”
Section: Introductionmentioning
confidence: 98%